Abdominal obesity and high-sensitivity C-reactive protein level among Malay obese adults in Kuantan, Malaysia - Shahadan, Siti Zuhaidah; Daud, Azlina; Md. Isa, Muhammad Lokman; Mohd Rasani, Ali Aminuddin; Ibrahim, Muhammad; Draman, Samsul (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Introduction: Abdominal obesity and inflammation are two independent risk factors for cardiovascular disease. However, the inter-relationship between these two factors among Malay population is fragmented. The purpose of this study is to determine the association between waist circumference as a measure of abdominal obesity and high-sensitivity C-reactive protein as an indicator of inflammation status among Malay obese adults in Kuantan, Pahang.